THE TRILOBITE FAMILY NILEIDAE: MORPHOLOGY AND CLASSIFICATION - Whittington H.B. (My University, 2003)
Species of genera currently referred to Nileidae are reviewed, and those of Hemibarrandia, Lakaspis, Peraspis and Symphysurina are excluded from the family. Nileidae are united in having a distinctive form of the hypostome, the glabellar organ, in the shallowness or absence of external furrows on the axial and pleural regions, and in the development of strong ventral ridges on the axial region. It is contended that the glabellar organ of nileids and illaenids may not be homologous with the glabellar tubercle of asaphids, that the median ventral suture is not exclusively a character of Asaphina, and doubt is cast on the identification of an asaphoid protaspis as being that of Nileus. These arguments provide a case for allying Nileidae with the Illaenidae, rather than with the Asaphina.
Keywords: TRILOBITA; NILEIDAE; MORPHOLOGY; CAMBRO-ORDOVICIAN; Paleozoic::Ordovician; Paleozoic::Cambrian; Палеозой::Кембрийская; Палеозой::Ордовикская